Penggunaan Playing Palisade Cocard dalam Perbaikan Hasil Belajar Matematika pada Sekolah Dasar - Millenia Anisa Putri; Heru Purnomo (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2022)
This study aims to improve students' mathematics learning outcomes. To reveal information about strategies and media, improve learning effectiveness through Playing Palisade Cocard. This study uses the observation method which contains four items during the learning process and the results of the competency test through tests and Student Activity Sheets (LKS) after each lesson. The findings of Classroom Action Research (CAR) after being analyzed showed that information obtained from students who reached the minimum completeness criteria (KKM) from 30 people before the cycle was carried out was 43.3% (13 people) with an average value of 67.9. After the first cycle of action increased to 66.7% (20 people) with an average of 78.3, an increase of 23.3% (7 people). While the implementation of cycle 2, the learning outcomes of students became 76.7% (23 people) with an average of 81.7, an increase of 10% (3 people). Overall, the mathematics learning outcomes of class II students during action research have increased by 33.3% (10 people).